THE EFFECT of SERIES of PICTURES MEDIA on STUDENTS’ ACHIEVEMENT in WRITING NARRATIVE TEXT - Naomi Lamtio Hutapea; Anni Holila Pulungan (Universitas Negeri Medan, 2013)
This study deals with the effect of using media Series of Pictures on students’ achievement in writing narrative text. The method of the research was quasi experimental design. Population of the study was grade XI of SMA BUDI MURNI. Two classes were chosen as purposive sampling. The classes were divided into two group was taught by using series of pictures and the control group without using the picture. The data were acquired by administered the pre-test and post-test. The data were analyzed by using SPSS 17.00. The mean score of the control group in pretest = 40.46, experimental group = 40.40. In post-test, mean score of the control group =46.94 while the experimental group =53.71.